Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.4049/jimmunol.1401683
|View full text |Cite
|
Sign up to set email alerts
|

The T Cell Repertoire–Diversifying Enzyme TSSP Contributes to Thymic Selection of Diabetogenic CD4 T Cell Specificities Reactive to ChgA and IAPP Autoantigens

Abstract: Multiple studies highlighted the overtly self-reactive T cell repertoire in the diabetes-prone NOD mouse. This autoreactivity has primarily been linked to defects in apoptosis induction during central tolerance. Previous studies suggested that thymus-specific serine protease (TSSP), a putative serine protease expressed by cortical thymic epithelial cells and thymic dendritic cells, may edit the repertoire of self-peptides presented by MHC class II molecules and shapes the self-reactive CD4 T cell repertoire. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…Interestingly, we found that although the regulation of Tssp expression during thymic cDC2 differentiation is conserved between B6 and NOD mice, its expression is significantly higher in the cDC1 subset of B6 mice as compared with NOD mice. The biological significance of this difference is unclear given that TSSP limits the presentation of self-antigen by thymic cDCs and consequently the negative selection of the corresponding CD4 T cell (16)(17)(18)20). Second, we found that Ctsl expression is barely detectable in pre-cDCs and further extinguished in the two cDC subset regardless of their tissue origin or whether cDCs are generated in in vitro cultures of BM with the exception of thymic cDC2, which maintain the low expression level of their BM precursor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, we found that although the regulation of Tssp expression during thymic cDC2 differentiation is conserved between B6 and NOD mice, its expression is significantly higher in the cDC1 subset of B6 mice as compared with NOD mice. The biological significance of this difference is unclear given that TSSP limits the presentation of self-antigen by thymic cDCs and consequently the negative selection of the corresponding CD4 T cell (16)(17)(18)20). Second, we found that Ctsl expression is barely detectable in pre-cDCs and further extinguished in the two cDC subset regardless of their tissue origin or whether cDCs are generated in in vitro cultures of BM with the exception of thymic cDC2, which maintain the low expression level of their BM precursor.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we showed that thymic cDCs uniquely express the thymus-specific serine protease (TSSP). In thymic cDCs, TSSP limits the presentation of several self-antigens and thus limits the deletion of self-reactive CD4 T cells (16)(17)(18)(19). Consequently, TSSP-deficient non-obese diabetic (NOD) mice are completely protected from autoimmune diabetes and develop less severe experimental autoimmune encephalomyelitis (16,20).…”
Section: Introductionmentioning
confidence: 99%
“…We had shown previously that, likewise, lack of TSSP expression by thymic APCs favors the deletion of several islet-reactive CD4 T cells and, therefore, leads to complete protection from autoimmune diabetes (28)(29)(30). Hence, TSSP significantly curtailed the peptide repertoire presented by I-A g7 -expressing thymic DCs and, thereby, predisposed to autoimmunity.…”
Section: Downloaded Frommentioning
confidence: 96%
“…Tssp-deficient (Tssp˚) B6 and NOD (NOD Tssp˚), NOD wild-type (WT), NODscid, Tssp˚NODscid, NOD-Tcra-deficient (NOD Ca˚), and TsspN OD Ca˚mice have been described previously (24,28). For generation of bone marrow (BM) chimeras, 10-12-wk-old NOD Ca˚and Tssp˚NOD Cam ice were irradiated (9.5 Gy) the day before reconstitution with 8 3 10 6 T cell-depleted NOD WT BM cells mixed at a 3:1 ratio with NODscid or Tssp˚NODscid BM cells, as previously described (30). This ratio is sufficient to induce deletion of islet-reactive CD4 T cells by TSSPdeficient APCs (28)(29)(30)(31).…”
Section: Mice and Bone Marrow Chimerasmentioning
confidence: 99%
See 1 more Smart Citation